2012
DOI: 10.2152/jmi.59.261
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve endocarditis complicated by perivalvular abscess

Abstract: : A 37-year-old man presenting with fever and chest pain was admitted to our hospital. Electrocardiogram showed sinus tachycardia and complete left bundle branch block. Transthoracic echocardiogram showed infective endocarditis in the bicuspid aortic valve, complicated by multiple hyperechoic vegetations and severe aortic regurgitation. Blood cultures were negative and intravenous empiric antibiotic therapy was begun. However, fever lasted for 7 days and follow-up echocardiography revealed a newly emerged peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Previous case reports have shown the presence of aortic root abscess with conduction disturbances [8]. In one of the reports, aortic root abscess was associated with new-onset complete right bundle branch block (RBBB) with prolonged PR interval, which eventually changed into a left bundle branch block (LBBB) morphology with features of atrioventricular (AV) dissociation followed by alternating bundle branch block on the second day [9]. While in the other case report patient had an aortic root abscess with sinus tachycardia and LBBB in EKG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous case reports have shown the presence of aortic root abscess with conduction disturbances [8]. In one of the reports, aortic root abscess was associated with new-onset complete right bundle branch block (RBBB) with prolonged PR interval, which eventually changed into a left bundle branch block (LBBB) morphology with features of atrioventricular (AV) dissociation followed by alternating bundle branch block on the second day [9]. While in the other case report patient had an aortic root abscess with sinus tachycardia and LBBB in EKG.…”
Section: Discussionmentioning
confidence: 99%
“…Kahveci et al reported peri annular complications in 64% of BAV IE patients [12]. Additionally, BAV is an independent risk factor for abscess formation in aortic valve infective endocarditis (IE), increasing the likelihood of surgical intervention [9]. According to the American College of Cardiology/American Heart Association Task Force Practice Guidelines, early surgical intervention is indicated in IE in the presence of valve dysfunction causing heart failure, IE caused by resistant organisms including S. aureus, presence of heart block or abscess, or a presence of persistent infection.…”
Section: Discussionmentioning
confidence: 99%